2018
DOI: 10.1016/j.jvs.2017.06.094
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of endovascular repair for descending thoracic aortic aneurysms

Abstract: Long-term (12-year) aorta-specific survival after on-label endovascular repair of degenerative descending thoracic aneurysms in nonsyndromic patients is excellent (96%) with sustained protection from rupture, and a low rate of reintervention owing to endoleak (7%). Endovascular repair should be considered the treatment of choice for this pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 26 publications
(29 reference statements)
1
49
0
1
Order By: Relevance
“…After database searching and evaluation, four papers based on four studies met the inclusion criteria for meta-analysis, which provided data for TEVAR only. 7,15e17 In addition, five further studies with inclusion potential (showing odds or hazard ratios for sex) were identified, of which one reported TEVAR data only, 18 and four reported both TEVAR and open repair data, 19e22 although none had published sex specific data. Therefore, the authors were contacted and three were able to provide further details, 18,19,22 allowing inclusion of these three studies, giving a total number of seven studies for the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After database searching and evaluation, four papers based on four studies met the inclusion criteria for meta-analysis, which provided data for TEVAR only. 7,15e17 In addition, five further studies with inclusion potential (showing odds or hazard ratios for sex) were identified, of which one reported TEVAR data only, 18 and four reported both TEVAR and open repair data, 19e22 although none had published sex specific data. Therefore, the authors were contacted and three were able to provide further details, 18,19,22 allowing inclusion of these three studies, giving a total number of seven studies for the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…7,15e17 In addition, five further studies with inclusion potential (showing odds or hazard ratios for sex) were identified, of which one reported TEVAR data only, 18 and four reported both TEVAR and open repair data, 19e22 although none had published sex specific data. Therefore, the authors were contacted and three were able to provide further details, 18,19,22 allowing inclusion of these three studies, giving a total number of seven studies for the meta-analysis. However, the additional data received from the nationwide German study revealed that the minority population, who had been treated by open repair, had a much younger mean age, with wider standard deviation, than other studies, particularly for men, implying that many patients <55 years had been included.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 It should be noted that, in many cases, the LSA can be only partially covered so as to gain additional proximal seal, yet without significant interruption of antegrade flow. 7 Our practice is to place bilateral radial arterial lines in all cases where either full or partial LSA coverage is planned, 10 and for those cases with partial coverage, to confirm preservation of left radial arterial line pulsatility after endograft deployment. Intraoperative neurophysiologic monitoring with motor-and sensory-evoked potentials is likewise used 12 and should remain intact after partial LSA endograft coverage.…”
Section: G Chad Hughes MDmentioning
confidence: 99%
“…17 According to recent reports, the 30-day mortality rate following TEVAR was 4 to 4.7%, occurrence rate of stroke was 0.6 to 2.7%, and occurrence rate of SCI was 0.5 to 3.2%. [18][19][20] Although endoleaks, which are the most common cause of reintervention, occurred in 6.4 to 10.5% of cases, the long-term survival and freedom rate from ARD seem to be acceptable.…”
Section: Descending Thoracic Aortic Aneurysmmentioning
confidence: 99%